Bundling for Flexibility and Variety: An Economic Model for Multiproducer Value Aggregation - Bhargava, Hemant K. (Management Science, 2021)
Many markets feature an economic structure in which value is cocreated by multiple producers and aggregated into a common bundle by a producer-consortium or independent firm. Examples include in-home video entertainment, technology goods and services, multisourced data platforms, and patent pools. This paper develops an economic model to study demand, production choices, revenue sharing, and relative market power in such markets. Producers in these markets are not rivalrous competitors in the usual zero-sum sense, because output of each casts an externality on production decisions of others and total market demand expands with total output, albeit with diminishing returns. This property allows multiple producers to flourish in equilibrium (versus just one with the most favorable technological or cost structure), and more so when the market expands less quickly with total output. Equilibrium production quantities of competitors are strategic complements, yet competition between producers does manifest itself, for example, if one acquires better production technology (i.e., makes value units at lower cost) then the equilibrium production levels of other producers are reduced. Insights are also derived for alternative market structures, for example, producers have more output and earn higher profit when organized into a distribution consortium (e.g., Hulu or consortia of zoos or museums) versus relying on a separate retailer. Mergers between producers have similar effect. The formulation enables us to rigorously answer economic questions ranging from pricing, revenue sharing, and production levels in a static setting, to market dynamics covering both the causes and effects of changes in industry structure. This paper was accepted by Chris Forman, information systems.